Active Sites and Mechanism of Oxygen Reduction Reaction Electrocatalysis on Nitrogen‐Doped Carbon Materials. Issue 13 (22nd October 2018) - Singh, Santosh K.; Takeyasu, Kotaro; Nakamura, Junji
Abstract: The oxygen reduction reaction (ORR) is a core reaction for electrochemical energy technologies such as fuel cells and metal–air batteries. ORR catalysts have been limited to platinum, which meets the requirements of high activity and durability. Over the last few decades, a variety of materials have been tested as non‐Pt catalysts, from metal–organic complex molecules to metal‐free catalysts. In particular, nitrogen‐doped graphitic carbon materials, including N‐doped graphene and N‐doped carbon nanotubes, have been extensively studied. However, due to the lack of understanding of the reaction mechanism and conflicting knowledge of the catalytic active sites, carbon‐based catalysts are still under the development stage of achieving a performance similar to Pt‐based catalysts. In addition to the catalytic viewpoint, designing mass transport pathways is required for O2 . Recently, the importance of pyridinic N for the creation of active sites for ORR and the requirement of hydrophobicity near the active sites have been reported. Based on the increased knowledge in controlling ORR performances, bottom‐up preparation of N‐doped carbon catalysts, using N‐containing conjugative molecules as the assemblies of the catalysts, is promising. Here, the recent understanding of the active sites and the mechanism of ORRs on N‐doped carbon catalysts are reviewed. Abstract : The development of metal‐free oxygen reduction reaction (ORR) catalysts based on N‐doped graphene, with high‐density active sites, is highly desirable. These catalysts, with acquired characteristics, are achievable through strategic design, via application of the combined knowledge of theoretical and experimental results. The homogeneously doped pyridinic N and the controlled catalyst surface hydrophobicity play a critical role in realizing high‐performance ORR catalysts.